FINANCIAL DIAGNOSTICS OF BUSINESS ENTITIES IN CONDITIONS OF ECONOMIC INSTABILITY - MATVIYCHUK, Lesia; MAKAROVA, Kseniia; KULIAS, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the conceptual foundations of the formation and implementation of a financial diagnostics system for an enterprise in conditions of economic uncertainty. The theoretical aspects of financial diagnostics are investigated. The essence of the concept of “financial diagnostics” is analyzed. It is determined that in economic literature, the concept of “financial diagnostics” is interpreted ambiguously, which indicates its multidimensionality and complexity.  The author proposes an approach to interpreting this concept, which allows financial diagnostics to be interpreted as a multidimensional, systematic process that combines the analytical, managerial, informational, and prognostic components of this concept. In economic literature, the terms “financial condition diagnostics” and “financial diagnostics” are often used in parallel during analytical procedures aimed at researching and evaluating the financial condition of an enterprise. This identification is due to the commonality of the object of study, but each of the concepts has its own semantic emphases and methodological features that determine the specifics of their application in the system of financial analysis and management diagnostics. In unstable economic conditions, financial diagnostics is aimed not only at assessing profitability or solvency, but also at identifying vulnerabilities, minimizing risks, and planning the sustainable development of the enterprise.The main characteristics of financial diagnostics in conditions of economic instability are presented. When conducting financial diagnostics, it is necessary to accurately assess the real need for choosing one method or another, correlating it with the complexity and scale of the problem situation of the object being diagnosed. It has been determined that adapting the financial diagnostics system to the conditions of martial law is crucial for ensuring the effective operation of domestic enterprises. In such circumstances, particular attention should be paid to strengthening control over financial risks, reviewing and adjusting financial strategies, and improving methods for assessing the liquidity and solvency of enterprises.
Keywords: financial diagnostics; economic instability; functions of financial diagnostics; principles of financial diagnostics; risks